Impact of Entrepreneurship on Economic Development in Nigeria - Omotayo, Vincent Adewale; Adeyinka, Adewole Joseph; Kayode Kadiri, Ibrahim; Attah, Eleojo Vincent (Acta Universitatis Danubius. Œconomica, 2024)
Entrepreneurship is seen as a significant factor used in modern economies for wealth creation, improvement in the standard of living, and the development of the economy. Despite these loadable roles, its impact in the attainment of required development has not been well felt in Nigeria. This study examined the impact of entrepreneurship on economic development in Nigeria. Annual time series data spanning from 1992 to 2022, analysed with ARDL techniques was employed. Rate of self-employment existing in the country was used to proxy entrepreneurship. Contribution of SMEs, private sector credit and inflation rate were also added in the model while human development index was used to represent economic development The result showed that self-employment rate is positive but insignificant in the short-run while its impact on economic development in the long-run is significant. Contribution of SME and credit to private sector is positive but insignificant on the long-run while the impact of inflation rate is inversely related. This indicated that government in conjunction with monetary authorities should formulate and implement sound economic policy that will make entrepreneurship to strive; this should not be done without taken cognizance of macroeconomic variables. More importantly, the financial institutions especially deposit money banks should be made to support entrepreneurship development by providing the start-up funds for entrepreneur at a reduced or concessionary rate.